Letramento em Saúde Individual e Organizacional: Determinantes para Implementação de Programa de Educação em Dor Crônica na Saúde Pública - Sales, Paula Torrezani (2024)
Chronic musculoskeletal pain is a clinical condition characterized by functional limitations in the patient's routine and disabilities, as well as psychosocial repercussions. The literature recommends multimodal management with an emphasis on self-management approaches for coping with chronic pain and working on self- efficacy. The effectiveness of interventions is influenced by contextual determinants, such as the health literacy (HL) of the individual and the health system. Methods: This is a cross-sectional analytical observational study, analyzing the influence of individual and organizational health literacy as contextual determinants in the implementation of a pain education program in a municipal health service. Patients with chronic musculoskeletal pain were assessed in terms of functional, communicative and critical literacy, as well as self-efficacy, pain intensity and functional impact. Professionals working in routine primary care (PHC) and medium complexity care were assessed on their beliefs and attitudes towards chronic pain. Results: Patients had a high level of self-efficacy and all domains of the LS. The analysis showed a direct association between these parameters and an inverse association with the interference of pain in the routine. However, non-specialist pain professionals had dysfunctional beliefs about caring behaviors and curing chronic pain. Conclusion: Patients showed positive cognitive skills for effective self-management of chronic pain in a PHC pain education program, but routine care professionals need training through continuing education programs and communication skills training.